Complementary Therapy: Citrus Aromatherapy for pain - Karolin Adhisty (Conferences of Medical Sciences Dies Natalis, 2020)
Pain is an unpleasant sensory sensation that can coincide with the onset of the disease. This pain will cause a psychological condition that will disrupt the daily life of the patient if it is not treated immediately. Health workers will certainly provide interventions that can be used by patients and their families to support this reduction in sensation. A complementary action that can be used to reduce this pain perception is a citrus aromatherapy. Citrus aromatherapy has a complete content not only relaxes the mind but also inhibits pain inhibitors so that the perception of pain can be immediately reduced. The pain decrease perception will certainly improve the quality of life of patients after the disease, both acute and chronic.